A survey of undergraduate medical students’ knowledge and attitudes about gender bias: the Newfoundland and Labrador perspective - Erika Maxwell; Gillian Sheppard; Yanqing Yi (Canadian Medical Education Journal, 2024)
Background: Female physicians and patients experience gender bias in healthcare. The purpose of this research is to explore medical students’ gender bias toward physicians and patients and whether their bias varies by gender.